Serum Liver Enzyme Patterns in Pediatric Hepatitis: A Systematic Review: Serum Liver Enzyme Patterns in Pediatric Hepatitis - Ibrahim, .; Hussain, Ansar; Iqbal, Mohammad; Khan, Jalil; Hamidullah, .; Ahmad, Tanveer (Pakistan Journal of Health Sciences, 2025)
Patterns of serum aminotransferases, alanine aminotransferase (ALT), and aspartate aminotransferase (AST) offer essential insights into the etiology and severity of pediatric hepatitis. Recent epidemiologic shifts, including adenovirus- and AAV2-associated cases, have highlighted the need for an updated synthesis of biochemical trajectories in children. Objectives: To systematically review published data (2018–2024) describing serum ALT and AST patterns in pediatric hepatitis across classical and emerging etiologies. Methods: Following PRISMA 2020 guidelines, PubMed, Scopus, and Web of Science were searched for English-language original studies reporting ALT/AST levels in children with hepatitis. Reviews, meta-analyses, and non-original reports were excluded. Methodological quality was assessed using the Newcastle–Ottawa Scale (NOS) for cohort studies and the Joanna Briggs Institute (JBI) checklists for cross-sectional and case-series designs. Extracted data included study characteristics, population details, enzyme levels, and clinical outcomes. Due to heterogeneity in design and reporting, findings were synthesized narratively. Results: Fourteen studies comprising approximately 2,300 participants were included. Autoimmune hepatitis demonstrated sustained moderate-to-high ALT/AST elevations (300–2,400 U/L). Acute viral hepatitis A/E showed abrupt spikes typically exceeding 1,000 U/L with rapid normalization. Severe or non-A-E hepatitis and adenovirus/AAV2-associated cases displayed the most extreme enzyme surges, with peaks occasionally surpassing 5,000 U/L. Most studies showed moderate overall quality but consistently low measurement bias. Conclusions: Serum ALT and AST remain robust and sensitive markers of pediatric hepatocellular injury, with distinct kinetic profiles across etiologies. Standardized, multicenter studies are needed to refine biochemical thresholds and enhance diagnostic interpretation.